Replik - Thaning, Kaj (Grundtvig-studier, 1992)
A Reply By Kaj Thaning In this article the writer protests against what he calls »two attacks on his thesis » Man First - «« (1963). First, against Regin Prenter’s review of this book, which is quoted in J.H. Schjørring’s obituary of Prenter, then against W.Michelsen’s article » The Way from Force to Freedom in Grundtvig’s Life and Works«, both printed in Grundtvig Studier 1991. Thaning claims that the word .conversion. can be used both about turning to God and about turning to His Creation, which Grundtvig did in » Norse Mythology«, 1832. According to Thaning, Prenter has not rendered it probable that this conversion was provoked in Grundtvig by »the unshakable fact of the Church«.In his article, W. Michelsen refers to » Handbook on World History« I (1833), in which Grundtvig states that for »school use« he now prefers the Greek view of human life and history to the mosaic-Christian, because the Greek view lends itself more easily to being »practised scientifically«, but that he still considers the Mosaic-Christian view »the only divine, true, and eternal one«. Thaning claims, however, that from 1832 the word .view. denotes a contrast to the Christian »faith«. The Biblical view was of no avail on Greek soil, Thaning claims. In 1833 Grundtvig went over to » Polybius’s heathen view of history«, which built on the contrast between the truth and the lie. As he could not employ simultaneously the three concepts, a Greek view of history, a Biblical view, and the Christian faith, »the Biblical view now slips over to the side of the Church and becomes identical with faith (divine, true, and eternal)«. In 1832, it is true, it was called divine because of its historical effects, but not eternal. It became so, however, in 1833. According to Thaning it was on this background that Grundtvig spoke about the contrast between church and school, faith and science, the temporal and the eternal.In 1833 - unlike in 1832 - the Mosaic-Christian view has moved on to the side of the Church, faith and eternity, and is thus not entitled to impose ecclesiastical forms on state and school. Here, according to Thaning’s understanding of Grundtvig, the Greek view must prevail, and it thus becomes clear that Grundtvig now »has a changed view of life«, which further appears from his enthusiastic outbursts at »thus escaping from the chaos of the thought-world that we have found ourselves in through many centuries«. It is this constant consideration for life which is the need of the time, Grundtvig says. And this is what Thaning calls a »conversion«.Thaning also finds that Michelsen’s reference to the small pamphlet .On the Clausen Libel Case. is misunderstood, as is also his conjecture about the influence of Clara Bolton on Grundtvig’s view of freedom. According to Thaning, it was in the pamphlet .On the Baptismal Covenant. that the idea arose that it would be possible for Grundtvig and his opponents to be in the state church together, if only it was made legal for the individual churchgoer to frequent a church of his own choice. Later this thought leads to the church being renamed, in Grundtvig’s usage, »a social institution« (1834).There should be a generous competition, not a struggle in the church, Thaning writes, »....the thought of the Biblical view as common to people of spirit, among them the naturalists (H.N. Clausen) means that Grundtvig can offer them reconciliation and cultural cooperation«, he says. » It is a manifestation of a new view in Grundtvig,« he claims, »and of the new view of freedom which is proclaimed in the dedicatory poem of Norse Mythology which ... is a far cry from the small pamphlet against Clausen from 1831«.